COVID-19 and the European Education Performance Decline: A Focus on Primary School Children's Reading Achievement between 2016 and 2021 - Sylke V. Schnepf; Silvia Granato (Institute of Labor Economics (IZA), 2023)
This study uses the Progress in International Reading Literacy Study (PIRLS) data, the only cross-national data having measured educational achievement during the COVID-19 pandemic, to investigate educational achievement decline of fourth graders across 21 European countries between 2016 and 2021. Learning decline estimated with PIRLS data is not only composed of learning loss due to COVID-19 but also European performance trends and national policy changes. The study illustrates the education performance decline in Europe by providing information on 20 year reading achievement trends, average performance declines and increasing number of the share of low performing students across European countries. Results of previous national counterfactual impact evaluation studies measuring learning decline in languages due to COVID-19 are compared to PIRLS reading achievement declines between 2016 and 2021. Furthermore, the study examines recent developments of educational inequalities within Europe by first comparing countries' education distributions between 2016 and 2021 and second by investigating changes in the share of children lacking important reading skills by socio-economic background.
Keywords: I21; I24; 330; COVID-19; pandemic; educational inequalities; school; PIRLS; Europe